A high-performance catalyst for the gas-phase synthesis of morpholine and its preparation method
The catalyst is prepared by using activated alumina support and copper-nickel active components in the morpholine production process, combined with the uniform precipitation method of urea precipitant, which solves the problems of low catalytic activity and environmental pollution, and achieves efficient and environmentally friendly morpholine synthesis.
Patent Information
- Application Number
- CN202310383155.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-11
- Publication Date
- 2025-07-01
- Estimated Expiration
- 2043-04-11
AI Technical Summary
In the existing morpholine production process, the catalyst has low catalytic activity and poor thermal stability, and the traditional process has problems of environmental pollution and high equipment costs.
The CuO/NiO@Al2O3 catalyst is prepared by uniform precipitation method to improve catalytic performance and environmental friendliness.
It improves the conversion rate of diethylene glycol and the selectivity of morpholine, reduces the catalyst loading volume and equipment cost, and has no pollution in the process and is environmentally friendly.
Smart Images

Figure CN116510734B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of industrial catalysis, and particularly to a high-performance catalyst for gas-phase synthesis of morpholine and a preparation method thereof. Background Art
[0002] Due to its special oxygen-nitrogen heterocyclic structure, morpholine is widely used as an important fine chemical intermediate in rubber, corrosion inhibitors, pharmaceuticals, etc. With the continuous expansion of the uses of morpholine, its demand has increased year by year, and the price has been rising. The traditional production processes of morpholine mainly include the strong acid dehydration method of diethanolamine, the catalytic ammoniation method of ethylene oxide, the dehydration cyclization method of diethylene glycol amine, and the catalytic ammonolysis cyclization method of diethylene glycol. Among them, the low-pressure ammonolysis cyclization method of diethylene glycol (DEG) has become the main morpholine synthesis process route for domestic and foreign manufacturers due to its low raw material price and simple process flow. However, this method has certain equipment requirements, and there are also deficiencies such as low catalytic activity of the catalyst and poor thermal stability.
[0003] At present, the vast majority of industrial morpholine production uses the low-pressure gas-phase method of diethylene glycol. Developing high-performance catalysts and improving reaction process conditions are very important for the production of morpholine. In current research reports, the morpholine synthesis catalysts mainly use the impregnation method and the traditional co-precipitation method. For the morpholine catalyst prepared by the impregnation method recorded in relevant literature, under optimized conditions, the single-pass conversion rate of diethylene glycol reaches 95%, and the selectivity of morpholine is above 85%. However, due to the small amount of active components loaded by the impregnation method, the performance of catalytic synthesis of morpholine is low. At the same time, the catalyst loading is large, and the required equipment cost is high. The traditional co-precipitation method generally uses NaOH or Na2CO3 as the precipitant. Its preparation process is not easy to control the pH, and a large amount of wastewater containing Na + will be generated during the suction filtration and washing process, which places a large burden on the environment. In summary, the current catalysts for morpholine synthesis are not ideal. Summary of the Invention
[0004] The purpose of the present invention is to provide a high-performance catalyst for gas-phase synthesis of morpholine and a preparation method thereof. The preparation process of the present invention does not require repeated washing with a large amount of water, is pollution-free, and is environmentally friendly; the precipitant urea has a wide source, and at the same time, like the raw material liquid ammonia, it can be co-produced with ammonia synthesis plants, with good economic benefits; in addition, the catalyst of the present invention has a high loading, a smaller volume of the catalyst of the same mass, a smaller average particle size of the active components of the catalyst, and better catalytic activity and stability.
[0005] In the first aspect of the present invention, a preparation method of a high-performance catalyst for gas-phase synthesis of morpholine is provided. Using activated alumina as the carrier, copper and nickel as the active components, and urea as the precipitant, the active components are deposited on the carrier by the homogeneous precipitation method to obtain CuO / NiO@Al2O3.
[0006] Preferably, the molar ratio of copper to nickel in the active component is 1-5:1; further, the molar ratio of copper to nickel in the active component is 1:1, 2:1, 3:1, 4:1, 5:1; more preferably, the molar ratio of copper to nickel in the active component is 3:1.
[0007] Preferably, the carrier accounts for 30%-50% of the catalyst mass fraction; further, the carrier accounts for 30%, 35%, 40%, 45%, 50% of the catalyst mass fraction; more preferably, the carrier accounts for 40% of the catalyst mass fraction.
[0008] Preferably, it includes the following steps:
[0009] S1. Crush, sieve and calcine activated alumina to obtain a pretreated carrier.
[0010] In a specific embodiment, crush commercial activated alumina and sieve it, take 200-240 mesh and place it in a muffle furnace. Heat it up to 700°C at a rate of 10°C / min in an air atmosphere and keep it for 3 hours. After natural cooling, obtain the pretreated carrier activated alumina.
[0011] S2. Weigh a certain proportion of copper-nickel nitrate, add deionized water to prepare a copper-nickel metal nitrate mixed solution, add a certain mass of the pretreated carrier and a precipitating agent, and stir and reflux for reaction.
[0012] Among them, the hydrolysis process of urea by heat is represented by formula (1):
[0013]
[0014] Using urea as the precipitating agent, the preparation process does not require a large amount of water for repeated washing, is pollution-free, and is environmentally friendly; the precipitating agent urea has a wide source, and at the same time, like raw material liquid ammonia, it can be co-produced with an ammonia synthesis plant, with good economic benefits; the loading is high, the volume of the catalyst of the same mass is smaller, and the catalytic activity and stability are better.
[0015] Preferably, the dosage of the precipitating agent is 3.75-6.25 times the molar amount of the copper-nickel metal nitrate mixed solution; further, the dosage of the precipitating agent is 3.75, 4, 4.25, 4.5, 4.75, 5, 5.25, 5.5, 5.75, 6, 6.25 times the molar amount of the copper-nickel metal nitrate mixed solution, and more preferably, the dosage of the precipitating agent is 5.25 times the molar amount of the copper-nickel metal nitrate mixed solution.
[0016] In a specific embodiment, the amount of urea is 3.75 to 6.25 times the molar amount of copper-nickel metal nitrate; further, the amount of urea is 3.75, 4.25, 4.75, 5.25, 5.75, 6.25 times the molar amount of copper-nickel metal nitrate, and more preferably, the amount of urea is 5.25 times the molar amount of the copper-nickel metal nitrate mixed solution.
[0017] For example, when the concentration of copper-nickel metal nitrate is 0.2 mol / L, the amount of urea is 0.75 mol / L to 1.05 mol / L; further, the amount of urea is 0.75 mol / L, 0.8 mol / L, 0.85 mol / L, 0.9 mol / L, 0.95 mol / L, 1 mol / L, 1.05 mol / L, 1.1 mol / L, 1.15 mol / L, 1.2 mol / L, 1.25 mol / L; more preferably, the amount of urea is 1.05 mol / L.
[0018] In a specific embodiment, in terms of mole fraction, Cu(NO3)2·3H2O and Ni(NO3)2·6H2O with a molar ratio of 1 to 5:1 are weighed, deionized water is added, and a copper-nickel metal nitrate mixed solution with a concentration of 0.2 mol / L is prepared. Urea with an amount 3.75 to 6.25 times the molar amount of copper-nickel metal nitrate is weighed and added to the mixed solution. 30% to 50% of the pretreated activated alumina with respect to the total mass fraction of the catalyst is added under stirring at 90 °C, and the reaction is stirred and refluxed for 24 h.
[0019] S3. After the reaction is completed, suction filtration is carried out, followed by drying and calcination to obtain CuO / NiO@Al2O3.
[0020] In a specific embodiment, after the mother liquor after the reaction is suction filtered, the filter cake is dried at 105 °C for 4 h, then heated to 550 °C at a rate of 10 °C / min in an air atmosphere and held for 6 h. After natural cooling, granulation is carried out to obtain CuO / NiO@Al2O3.
[0021] Preferably, the following steps are further included:
[0022] S4. The catalyst is fixed in the constant temperature zone of the reaction tube of the stainless steel high-pressure fixed bed reactor in the order of quartz wool - catalyst - quartz wool, the reaction tube is connected and the system airtightness is checked;
[0023] S5. Heat up to 300 °C in a nitrogen atmosphere, and then adjust the flow rate of 10% H2 / N2 mixed gas to 60 mL / min through a mass flow meter under normal pressure to reduce the catalyst for 4 h;
[0024] S6. After the reduction is completed, the temperature is lowered to the reaction temperature, and the system pressure is adjusted and maintained by a hydrogen pressure reducing valve and a system back pressure valve; the reaction hydrogen flow rate is controlled by a mass flow meter, and the liquid feed is controlled by a double plunger micro pump. At a certain feed space velocity of diethylene glycol, liquid ammonia and diethylene glycol are mixed and enter a vaporizer to be vaporized and then enter the reaction section. After passing through a condenser, gas-liquid separation occurs. Liquid products are taken every 0.5 h, and the conversion rate of diethylene glycol and the selectivity of morpholine are detected by gas chromatography analysis.
[0025] For the evaluation of the catalytic performance of the present invention, a self-assembled stainless steel high-pressure fixed bed reactor is used, and the catalyst is fixed in the reaction tube with quartz wool, which is more in line with industrial reality.
[0026] Preferably, the reaction temperature in step S6 is 210 - 250 °C; further, the reaction temperatures are 210 °C, 220 °C, 225 °C, 230 °C, 235 °C, 240 °C, 250 °C; more preferably, the reaction temperature is 230 °C.
[0027] Preferably, the system pressure in step S6 is 1.5 - 2.0 MPa; further, the system pressures are 1.5 MPa, 1.6 MPa, 1.7 MPa, 1.8 MPa, 1.9 MPa, 2.0 MPa; more preferably, the system pressure is 1.7 MPa.
[0028] Preferably, the feed space velocity of diethylene glycol in step S6 is 0.2 - 0.8 mL·g -1 ·h -1 ; further, the feed space velocities of diethylene glycol are 0.2 mL·g -1 ·h -1 , 0.3 mL·g -1 ·h -1 , 0.4 mL·g -1 ·h -1 , 0.5 mL·g -1 ·h -1 , 0.6 mL·g -1 ·h -1 , 0.7 mL·g -1 ·h -1 , 0.8 mL·g -1 ·h -1 ; more preferably, the feed space velocity of diethylene glycol is 0.6 mL·g -1 ·h -1 .
[0029] In the second aspect of the present invention, there is provided a high-performance catalyst for gas-phase synthesis of morpholine prepared by the preparation method of the high-performance catalyst for gas-phase synthesis of morpholine described above.
[0030] Advantages of the present invention:
[0031] (1) The high-performance catalyst for the gas-phase synthesis of morpholine prepared by the present invention has good catalytic performance, effectively improving the conversion rate of raw material diethylene glycol.
[0032] (2) The present invention uses urea as a precipitant, with a simple process and easy control; a large amount of wastewater containing Na + will not be generated during the preparation process, which is environmentally friendly.
[0033] (3) The raw materials of the present invention are easily obtained, and the preparation of the catalyst and its catalytic synthesis of morpholine can be co-produced with an ammonia synthesis plant. Description of the Drawings
[0034] In order to more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the following will briefly introduce the drawings required for use in the description of the specific embodiments or the prior art. Obviously, the drawings in the following description are some embodiments of the present invention. For those of ordinary skill in the art, without creative efforts, other drawings can also be obtained based on these drawings.
[0035] Figure 1 (a) is the SEM image of the catalyst CuO / NiO@Al2O3 in Experimental Example 2 of the present invention, with a resolution of 500 nm; Figure 1 (b) is the SEM image of the catalyst CuO / NiO@Al2O3 in Experimental Example 2 of the present invention, with a resolution of 200 nm;
[0036] Figure 2 is the XRD comparison chart of the catalyst CuO / NiO@Al2O3 and the commercial catalyst (CO-cat) in Experimental Example 2 of the present invention;
[0037] Figure 3 is the hydrogen temperature-programmed reduction chart of the catalyst prepared by the present invention and the commercial catalyst, where CO-cat refers to the commercial catalyst and HP-cat refers to the catalyst CuO / NiO@Al2O3 in Experimental Example 2;
[0038] Figure 4 is the detection chart of the catalytic product of the catalyst prepared by the present invention;
[0039] Figure 5 is the influence curve chart of the copper-nickel ratio on the performance of the catalyst prepared by the homogeneous precipitation method in Experimental Example 3 of the present invention;
[0040] Figure 6 is the influence curve chart of the carrier ratio on the performance of the catalyst prepared by the homogeneous precipitation method in Experimental Example 4 of the present invention;
[0041] Figure 7 is the influence curve chart of the urea concentration on the performance of the catalyst prepared by the homogeneous precipitation method in Experimental Example 5 of the present invention;
[0042] Figure 8 This is the high-pressure fixed-bed reactor device diagram in Experimental Example 6 of the present invention.
[0043] Explanation of reference numerals: 1. 10% H2 / N2 storage device; 2. Hydrogen storage device; 3. Nitrogen storage device; 4. Gas pressure reducing valve; 5. Ball valve; 6. Filter; 7. Gas mass flowmeter; 8. Liquid ammonia storage device; 9. DEG filter cup; 10. Double plunger micro metering pump; 11. Vaporizer; 12. Reactor; 13. Controller; 14. Condenser; 15. Gas-liquid separator; 16. Back pressure valve; 17. Globe valve. Detailed implementation manners
[0044] It should be noted that the following detailed description is illustrative and is intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those of ordinary skill in the technical field to which the present application belongs.
[0045] It should be noted that the terms used herein are only for describing specific implementation manners and are not intended to limit the exemplary implementation manners according to the present application. As used herein, unless the context clearly indicates otherwise, the singular form also includes the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, they indicate the presence of features, steps, operations, devices, components, and / or combinations thereof.
[0046] The technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are some, but not all, of the embodiments of the present invention. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative efforts shall fall within the protection scope of the present invention.
[0047] Embodiment 1
[0048] This embodiment provides a preparation method of a high-performance catalyst for gas-phase synthesis of morpholine. Using activated alumina as the carrier, copper nickel as the active component, and urea as the precipitating agent, the active component is deposited-precipitated onto the carrier by the homogeneous precipitation method to obtain a high-performance catalyst CuO / NiO@Al2O3 for gas-phase synthesis of morpholine.
[0049] In this embodiment, the specific preparation method includes the following steps:
[0050] (1) Crush the commercial activated alumina and screen it. Take 200-240 mesh and place it in a muffle furnace. Heat it to 700 °C at a rate of 10 °C / min in an air atmosphere and hold for 3 h. After natural cooling, the pretreated carrier activated alumina is obtained.
[0051] (2) Weigh Cu(NO3)2·3H2O and Ni(NO3)2·6H2O with a molar ratio of 3:1 in terms of mole fraction, add deionized water, and prepare a mixed solution of copper-nickel metal nitrate with a concentration of 0.2 mol / L. Add urea with a molar amount 5.25 times that of the copper-nickel metal nitrate to the mixed solution, and add 40% of the pretreated activated alumina with respect to the total mass fraction of the catalyst under stirring at 90 °C, and react for 24 h.
[0052] (3) After filtering the mother liquor after the reaction, place the filter cake in an oven and dry it at 105 °C for 4 h. The dried catalyst intermediate is calcined in a muffle furnace, heated to 550 °C at a rate of 10 °C / min and maintained for 6 h. After natural cooling, the target catalyst CuO / NiO@Al2O3 is obtained, granulated and sieved to 40 - 80 mesh for standby, denoted as HP-cat.
[0053] In this example, it also includes the step of evaluating the catalyst activity:
[0054] (4) Fix 2 g of the catalyst in the constant temperature zone of the reaction tube of a stainless steel high-pressure fixed bed reactor in the order of quartz wool - catalyst - quartz wool, connect the reaction tube and check the airtightness of the system.
[0055] (5) Heat up to 300 °C under a nitrogen atmosphere, and then adjust the flow rate of 10% H2 / N2 mixed gas to 60 mL / min through a mass flow meter under normal pressure to reduce the catalyst for 4 h.
[0056] (6) After the reduction, cool down to the reaction temperature of 230 °C, and adjust the reaction pressure of the system to 1.7 MPa and maintain it through a hydrogen pressure reducing valve and a system back pressure valve; the reaction hydrogen flow rate is controlled by a mass flow meter, and the liquid feed is controlled by a double plunger micro pump, with a feed space velocity of diethylene glycol of 0.6 mL·g -1 ·h -1 . The liquid ammonia and diethylene glycol are mixed and then enter the vaporizer to be vaporized and enter the reaction section. After passing through the condenser, gas-liquid separation is carried out. Take the liquid product every 0.5 h, and analyze and detect the conversion rate of diethylene glycol and the selectivity of morpholine by gas chromatography.
[0057] In the catalytic performance evaluation of the present invention, a self-assembled tubular reactor is used, and the catalyst is fixed in the reaction tube with quartz wool, which is more in line with industrial reality; the preparation process of the catalyst described in the present invention is simple, and there is no need for repeated washing with a large amount of water during the preparation process, without pollution and friendly to the environment; the precipitant urea has a wide source, and at the same time, like the raw material liquid ammonia, it can be co-produced with synthetic ammonia plants, with good economic benefits; the loading amount is high, the volume of the catalyst of the same mass is smaller, and the catalytic performance is better.
[0058] Example Two
[0059] This example provides a high-performance catalyst CuO / NiO@Al2O3 for the gas-phase synthesis of morpholine prepared by the preparation method of Example 1.
[0060] The morphology was observed using a scanning electron microscope (SEM). Figure 1 The surface morphology structure of the catalyst CuO / NiO@Al2O3 was shown. The results indicated that the catalyst CuO / NiO@Al2O3 prepared by the homogeneous precipitation method using urea as the precipitant had a porous and loose structure on the surface, with a more uniform morphology and smaller particle size.
[0061] The crystal structure of the catalyst (HP-cat) prepared by the invention and the commercial catalyst (CO-cat: from Sichuan Hongpeng New Materials Co., Ltd.) was analyzed using an X-ray diffractometer (XRD). Figure 2 The XRD comparison spectra of the catalyst of the invention and the commercial catalyst were shown. Characteristic diffraction peaks appeared at 2θ of 35.5° and 38.7°, corresponding to the CuO standard card (PDF#45-0937). In addition, the characteristic diffraction peaks of nickel and its oxides were not detected, which was attributed to the high dispersion of nickel oxide in the catalyst or its crystallinity being lower than the detection limit. The average particle size of CuO in the catalyst was calculated by the Scherrer formula (see Table 1): the average particle size of CuO on the (11-1) plane of the commercial catalyst was 28.03 nm, and the average particle size of CuO on the (111) plane was 19.90 nm; the average particle size of CuO on the (11-1) plane of the catalyst of the invention was 19.00 nm, and the average particle size of CuO on the (111) plane was 13.82 nm, indicating that the active components of the catalyst of the invention were uniformly dispersed and had a smaller average particle size. The catalyst of the invention had a smaller average particle size of CuO because the hydrolysis process of urea was relatively slow at a certain temperature and ammonia was gradually released, so there was no concentration gradient in the solution during the precipitation process, and the precipitation rate was controllable, making the dispersion of the active components more uniform and the average particle size smaller.
[0062] Table 1
[0063]
[0064] The reduction properties of the commercial catalyst (CO-cat) and the catalyst (HP-cat) prepared by the homogeneous precipitation method of the invention were studied using the hydrogen temperature-programmed technique. The study proved that the reduction properties of the catalyst had a very important influence on its catalytic activity. As Figure 3As shown in the figure, in the experimental test temperature range of 50 - 500 °C, both CO-cat and HP-cat showed a reduction peak, which was the reduction peak of CuO in the catalyst. Moreover, the peak top temperatures of CO-cat and HP-cat were lower than that of pure CuO by 293 °C. Among them, the reduction peak temperature of CO-cat was 231.9 °C, while the reduction peak temperature of the catalyst HP-cat prepared by the homogeneous precipitation method was 210.5 °C, lower than that of the commercial catalyst CO-cat. The shift of the reduction peak to a lower temperature indicates that the copper oxide particles dispersed on the catalyst surface are more easily reduced, which also means that the CuO particles in the HP-cat catalyst are smaller and have better dispersion. At the same time, the reduction peak of CO-cat is wider and the peak height is lower, indicating that the particle sizes of CuO in the CO-cat catalyst are not uniform, the particle size distribution is larger, there are large particle size particles, the dispersion degree of the active component is lower, the catalyst is more difficult to reduce, and the catalytic activity is lower. While HP-cat has a reduction peak with a lower reduction temperature and a more concentrated shape, which indicates that the particle size distribution of HP-cat is relatively uniform and concentrated, the catalyst is more easily reduced, and the catalytic activity is higher. This is consistent with other characterization results and catalytic performance evaluation results. The peak area of the reduction peak in the hydrogen temperature-programmed reduction of CO-cat is smaller, and its hydrogen consumption for reduction is smaller, which indicates that the loading amount of CuO in the catalyst is less, the copper sites available for catalytic reaction are fewer, resulting in low catalytic activity. The reduction peak area of HP-cat is larger, 3.6 times that of CO-cat, indicating that the catalyst prepared by the present invention has more loaded active components and higher catalytic activity.
[0065] The catalytic products of the catalyst of the present invention were detected. Figure 4 The results showed that: the peak at the retention time of 1.137 min was the solvent methanol, the peak at the retention time of 1.452 min was the product morpholine, the peak at the retention time of 2.045 min was the raw material diethylene glycol, and the peaks at the retention times of 1.231 min, 1.259 min, 1.688 min, 3.308 min, 4.595 min, 11.364 min, and 14.884 min were by-products. The results indicated that: the catalytic reaction of the catalyst prepared by the present invention had high selectivity for morpholine and few catalytic by-products.
[0066] Example 3
[0067] In this example, a copper-nickel bimetallic catalyst supported on activated alumina was prepared by the homogeneous precipitation method, and the performance changes of the catalyst were investigated in the range of the molar ratio of the active components copper to nickel of 1 - 5:1. The results are as follows Figure 5As shown in the figure: within the investigated range, as the copper-nickel ratio increases from 1:1 to 3:1, the conversion rate of diethylene glycol and the selectivity of morpholine also gradually increase. The conversion rate of diethylene glycol increases from 90.37% to 98.25%, and the selectivity of morpholine increases from 71.37% to 90.21%. When the copper-nickel ratio is 3:1, the conversion rate of diethylene glycol and the selectivity of morpholine reach the maximum. When the copper-nickel ratio continues to increase from 3:1, the conversion rate of diethylene glycol remains basically unchanged, but the selectivity of morpholine decreases accordingly. When the copper-nickel ratio reaches 5:1, the selectivity of morpholine is only 78.39%, which is 11.82% lower than that when the copper-nickel ratio is 3:1.
[0068] In this example, the catalyst activity evaluation conditions are: P = 1.7 MPa, T = 230 °C, LHSV (diethylene glycol feed space velocity) = 0.5 mL·g -1 ·h -1 , NH3 / DEG (molar ratio) = 10:1.
[0069] Example Four
[0070] In this example, using the pretreated activated alumina as the carrier, the influence of the carrier ratio on the catalyst performance is investigated. The results are as Figure 6 shown: within the investigated range, the carrier accounts for 30% to 50% (mass fraction) of the catalyst. When the carrier accounts for 30% of the total catalyst, the conversion rate of the raw material diethylene glycol is 92.261, while the selectivity of the target product morpholine is only 60.41%. As the carrier ratio increases from 30% to 40%, the conversion rate of the raw material diethylene glycol and the selectivity of the product morpholine also increase to 98.25% and 90.21% respectively, and the yield of the target product morpholine is the largest. After continuing to increase the carrier ratio, the conversion rate of diethylene glycol and the selectivity of morpholine decrease sharply.
[0071] In this example, the catalyst activity evaluation conditions are: P = 1.7 MPa, T = 230 °C, LHSV (diethylene glycol feed space velocity) = 0.5 mL·g -1 ·h -1 , NH3 / DEG (molar ratio) = 10:1.
[0072] Example Five
[0073] In this example, within the tested range, the influence of the precipitant concentration on the catalyst performance is investigated. The results are as Figure 7 shown: when the concentration of the copper-nickel metal nitrate mixed solution is 0.2 mol / L, as the amount of urea increases, the conversion rate of diethylene glycol in the catalytic synthesis of morpholine changes little, all above 98.77%, while the selectivity of morpholine shows a trend of increasing first and then decreasing, increasing from 64.59% when the amount of urea is 3.75 times the molar amount of metal nitrate to 92.75% when it is 5.25 times, and then gradually decreasing as the amount of urea further increases.
[0074] In this example, the catalyst activity evaluation conditions are: P = 1.7 MPa, T = 230 °C, LHSV (diethylene glycol feed space velocity) = 0.5 mL·g -1 ·h -1 , NH3 / DEG (molar ratio) = 10:1.
[0075] Example Six
[0076] The catalyst activity evaluation was carried out in a self-assembled stainless steel high-pressure fixed-bed reactor (as Figure 8 shown). The reaction tube had a diameter of 10 mm and a length of 400 mm. Weighed 2 g of catalyst was fixed in the isothermal zone of the stainless steel reaction tube in the order of quartz wool - catalyst - quartz wool. The reaction tube was connected and the system airtightness was checked. First, it was heated to 300 °C in the atmosphere of nitrogen (stored in the nitrogen storage device 3). Subsequently, after filtration through the filter 6 under normal pressure, the flow rate of the 10% H2 / N2 mixed gas in the 10% H2 / N2 mixed gas storage device 1 was adjusted to 60 mL / min by the gas mass flowmeter 7, and the catalyst was reduced for 4 h. After the reduction was completed, the temperature was lowered to the reaction temperature, and the system pressure was adjusted and maintained through the gas pressure reducing valve 4 for hydrogen, the ball valve 5, and the system back pressure valve 16. The flow rate of the reaction hydrogen (stored in the hydrogen storage device 2) was controlled by the gas mass flowmeter 7, the liquid feed was controlled by the double plunger micro metering pump 10, the liquid ammonia in the liquid ammonia storage device 8 was mixed with the diethylene glycol in the DEG filter cup 9 and then entered the vaporizer 11 to be vaporized and enter the reactor 12, which was controlled through the controller 13. The product passed through the condenser 14 and then through the gas-liquid separator 15 for gas-liquid separation. The liquid product was taken from the stop valve 17 every 0.5 h.
[0077] In this example, with 200 - 250 °C, 1.7 MPa, diethylene glycol feed space velocity 0.5 mL·g -1 ·h -1 , ammonia-alcohol ratio 10:1 as the reaction conditions, the influence of the reaction temperature on the catalyst performance was explored, and the results are shown in Table 2.
[0078] Table 2
[0079] Temperature / °C Conversion rate / % Selectivity / % 210 96.244 89.052 220 98.569 90.874 225 99.496 92.561 230 99.748 92.747 235 99.567 92.016 240 99.769 90.957 250 99.842 89.794
[0080] The results show that: as the temperature increases, the conversion rate of diethylene glycol shows a trend of first increasing and then decreasing, and the selectivity of morpholine shows a trend of first increasing and then decreasing. When the reaction temperature is 230 °C, the conversion rate of diethylene glycol is the largest and the selectivity of morpholine is the highest.
[0081] Example Seven
[0082] In this example, the method of Example Six was adopted, with 1.5 - 2.0 MPa, 230 °C, diethylene glycol feed space velocity 0.5 mL·g-1 ·h -1 With an ammonia - to - alcohol ratio of 10:1 as the reaction condition, the influence of reaction pressure on the catalyst performance was investigated, and the results are shown in Table 3.
[0083] Table 3
[0084] Pressure / MPa Conversion rate / % Selectivity / % 1.5 93.145 88.543 1.6 97.056 90.491 1.7 99.748 92.747 1.8 99.165 91.581 1.9 98.725 90.273 2.0 97.556 89.569
[0085] The results show that: with the increase of pressure, the conversion rate of diethylene glycol shows a trend of first increasing and then decreasing, and the selectivity of morpholine also shows a trend of first increasing and then decreasing. When the reaction pressure is 1.7 MPa, the conversion rate of diethylene glycol is the largest and the selectivity of morpholine is the highest.
[0086] Example 8
[0087] In this example, the method of Example 6 was adopted. With a diethylene glycol feed space velocity of 0.2 - 0.8 mL·g -1 ·h -1 , 230 °C, 1.7 MPa, and an ammonia - to - alcohol ratio of 10:1 as the reaction conditions, the influence of the diethylene glycol feed space velocity (LHSV) on the performance of three catalysts was investigated, and the results are shown in Table 4.
[0088] Table 4
[0089]
[0090]
[0091] The results show that: with the increase of the diethylene glycol feed space velocity, the conversion rate of diethylene glycol shows a trend of first increasing and then decreasing, and the selectivity of morpholine generally shows a trend of first increasing and then decreasing. When the diethylene glycol feed space velocity is 0.6 mL·g -1 ·h -1 , the conversion rate of diethylene glycol is the largest and the selectivity of morpholine is the highest.
[0092] Example 9
[0093] In this example, the thermal stability of the catalyst of the present invention was studied. After the catalyst was reduced, it was first fed for reaction at a high temperature of 290 °C for 5 h, and then cooled to 230 °C to investigate the change of the catalyst performance after the high - temperature reaction. The results show that the product yield decreased from 93.00% to 88.70%, but it still had relatively high catalytic activity.
[0094] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those of ordinary skill in the art should understand that they can still modify the technical solutions described in the foregoing embodiments, or perform equivalent replacements on some or all of the technical features; and these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. Application of a high-performance catalyst in the gas-phase synthesis of morpholine, characterized in that, Fix 2 g of the catalyst in the isothermal zone of the reaction tube of a stainless-steel high-pressure fixed-bed reactor in the order of quartz wool - catalyst - quartz wool, connect the reaction tube and check the airtightness of the system; Heat it to 300 °C under a nitrogen atmosphere, and then adjust the flow rate of the 10% H2 / N2 mixed gas to 60 mL / min through a mass flow meter under atmospheric pressure to reduce the catalyst for 4 h; After the reduction is completed, the reaction temperature is cooled to 230 °C, and the reaction pressure of the system is adjusted to 1.7 MPa by the hydrogen pressure reducing valve and the system back pressure valve and maintained; the reaction hydrogen flow rate is controlled by a mass flow meter, and the liquid feed is controlled by a double plunger micro pump at a feed space velocity of diglycol of 0.6 mL·g -1 ·h -1 . After the liquid ammonia and diglycol are mixed, they enter the vaporizer to be vaporized and then enter the reaction section. After passing through the condenser, gas-liquid separation occurs. The liquid product is taken every 0.5 h, and the conversion rate of diglycol and the selectivity of morpholine are detected by gas chromatography analysis; The specific preparation method of the catalyst includes the following steps: Crush activated alumina and sieve it, take 200 - 240 mesh and place it in a muffle furnace. Heat it to 700 °C at a rate of 10 °C / min in an air atmosphere and keep it for 3 h. After it cools naturally, the pretreated carrier activated alumina is obtained; Weigh Cu(NO3)2·3H2O and Ni(NO3)2·6H2O with a molar ratio of 3:1 in terms of mole fraction, add deionized water to prepare a copper-nickel metal nitrate mixed solution with a concentration of 0.2 mol / L. Add urea with a molar amount 5.25 times that of the copper-nickel metal nitrate to the mixed solution, and add 40% of the pretreated activated alumina based on the total mass fraction of the catalyst under stirring at 90 °C, and react for 24 h; After the mother liquor after the reaction is filtered by suction, place the filter cake in an oven and dry it at 105 °C for 4 h. The dried catalyst intermediate is calcined in a muffle furnace, heated to 550 °C at a rate of 10 °C / min and kept for 6 h. After it cools naturally, the target catalyst CuO / NiO@Al2O3 is obtained.
Citation Information
Patent Citations
Catalyst for hydrogenation of dimethyl oxalate to prepare methyl glycolate, preparation method and application thereof
CN101954288A
High-efficiency hydrogenation catalyst and method for preparing same
CN102764656A